Healthcare-seeking behaviour, barriers and mental health of non-domestic migrant workers in Singapore - Koh, Calvin J. (2017)
Background: Low-wage migrant workers are vulnerable to healthcare inequities. We sought to identify potential barriers to healthcare and risk factors for mental health issues in non-domestic migrant workers in Singapore, and identify high-risk subgroups. Methods: A cross-sectional, interviewer-administered survey of 433 non-domestic migrant workers was conducted at subsidised clinics and a foreign worker dormitory from July to August 2016. Questions assessed healthcare usage patterns, affordability issues, barriers to care and psychological distress using a validated screening scale (Kessler-6). Findings: Bangladeshi workers surveyed were more likely to be single, have more financial dependents, a lower level of education and salary and pay higher agent fees (p<0.01). 61.4% of workers reported that they had insurance, but had poor understanding of whether it covered inpatient/outpatient expenses. The majority of workers had not, or were not sure if they had, received information about company-bought insurance (72.4%). Among those who had, most reported that information was not in their native language (67.7%). Non-specific psychological distress was found in 21.9%, as estimated by the Kessler-6 scale. Multivariate analysis found that psychological distress was independently associated with Bangladeshi nationals (OR 2.98, 95% CI 1.58 to 5.62; p=0.001) and previous experience of financial barriers to healthcare (OR 3.86, 95% CI 2.25 to 6.62; p<0.0001). Interpretation: We identified gaps in non-domestic migrant workers' knowledge of healthcare coverage, and substantial financial barriers to healthcare. The Bangladeshi population in our study was at higher risk of such barriers and psychological distress. These represent areas for further research and intervention.